Fast pyrolysis of methyl ricinoleate in an inductively heated reactor coupled with atomization feeding. (25th July 2021) - Mao, Xiaoning; Xie, Qinglong; Yi, Xiaogen; Duan, Ying; Yu, Shangzhi; Wu, Zhenyu; Liang, Xiaojiang; Nie, Yong
Graphical abstract: Highlights: An inductively heated reactor was developed for MR pyrolysis to UAME and HEP. Atomization feeding was adopted using three pressure swirl nozzles. Temperature distribution of reactor determined by simulation was uniform. The highest UAME and HEP yields were 56.1 wt% and 60.2 wt%, respectively. Abstract: Undecylenic acid methyl ester (UAME) and heptanal (HEP) are important chemical intermediates, which can be produced from pyrolysis of methyl ricinoleate (MR). The temperature gradient existing in conventional tubular reactor for MR pyrolysis would cause the reduction of UAME and HEP yields. An inductively heated reactor coupled with atomization feeding was developed in this study and used for MR pyrolysis. Numerical simulation was first adopted to examine the effect of nozzle number on temperature distribution of the reactor. Results showed that uniform temperature distribution was achieved when three nozzles were used. The average temperature and the standard deviation of the reaction area were 496.54 °C and 6.34 °C respectively at the set temperature of 500 °C. Experimental tests of MR pyrolysis on the reactor were then performed using three nozzles. Results showed that MR conversion increased with the increasing temperature from 440 to 560 °C. The highest UAME and HEP yields of 56.1 wt% and 60.2 wt% respectively were achieved at 520 °C. The product yields were obviously higher than those obtained using conventional tubular reactor. It was mainly due to the uniform temperature distribution of reactor and rapid heating of feedstock by using the inductively heated reactor coupled with atomization feeding.